EFFECT OF PRENATAL YOGA ON ANXIETY, BLOOD PRESSURE, AND FETAL HEART RATE IN PRIMIGRAVIDA MOTHERS - Hamdiah Hamdiah; Ari Suwondo; Triana Sri Hardjanti; Ariawan Soejoenoes; M Choiroel Anwar (Belitung Nursing Journal, 2017)
Background: Pregnancy increases the risk of developing anxiety that may affect the fetus. Yoga is considered as an alternative therapy to reduce anxiety, blood pressure, and fetal heart rate. Objective: This study aimed to examine the effect of prenatal yoga on anxiety, blood pressure, and fetal heart rate in primigravida mothers. Methods: There were 39 primigravida mothers selected using purposive sampling, which divided into three groups - an experiment group with four-times prenatal yoga, an experiment group with eight-times prenatal yoga, and a control group. The Hamilton Rating Scale for Anxiety (HRSA) was used. Data were analyzed using One-way ANOVA and MANOVA. Results: There was a statistically significant difference of prenatal yoga on anxiety (p=0.005), systolic blood pressure (p=0.045), and fetal heart rate (p=0.010). However, there was no significant difference of prenatal yoga on diastolic blood pressure with p-value 0.586 (>0.05). Conclusion: There were significant effects of prenatal yoga on anxiety level, systolic blood pressure, and the fetal heart rates in primigravida mothers. The findings of this study can be an alternative treatment for midwife to deal with anxiety during pregnancy and an input for the class program of pregnant women to improve the quality of maternal and fetal health.